Modificação química de poli(ácido láctico) com monômeros vinílicos, por processamento reativo, visando ajuste molecular e sua utilização em blendas poliméricas - Rigolin, Talita Rocha (Universidade Federal de São Carlos, 2018)
Poly(lactic acid) (PLA) was modified with maleic anhydride (MA) or glycidyl methacrylate (GMA) in the presence of peroxide to assess the physical and chemical changes of the polymer during the reactive processing. Chemical modification of polymers with vinyl monomers can be seen as a great scientific challenge in order to obtain a material with adjustable physical and chemical properties due to changes in acidity, functionality and molar mass. The type of vinyl monomer (GMA and MA), peroxide (dicumyl peroxide and 2,5-dimethyl-2,5-di- (t-butylperoxy) hexane), pure or dispersed in CaCO3, and the monomer and peroxide concentration used were evaluated through an experimental design. Molar mass and acidity content were analyzed. Maleic anhydride grafting onto poly(lactic acid) (PLA) showed a decrease in the polymer molar mass and an increase in the acid content. However, when GMA is used in the functionalization of PLA, an increase in molar mass is observed with reduction of acidity of the polymer. PLA/PBAT blends were obtained in order to evaluate the efficacy of the chemical modification and the feasibility of the applied use of the modified PLA, either as the compatibilizer for the blend or as the matrix, depending on its molar mass and acidity content, in addition to in situ compatibilization with the different monomers. Oscillatory shear rheological tests and transmission electron microscopy (TEM) were used to evaluate how the different modified polymers performed in the morphology development and rheological properties of these blends. The morphology obtained was predominantly co-continuous and the viscosity ratio between the components predominated over a possible reduction of interfacial tension with the introduction of the vinyl monomers in the system. Results also showed that similar morphologies can be formed with the use of both monomers, GMA and MA, and that the procurement methodology of the blends can be adapted for the different monomers.
Chemical modification of poly(lactic acid) with vinyl monomers, by reactive processing, aiming at molecular adjustment and their use in polymer blends
Keywords: Modificação química; PLA; Processamento reativo; Chemical modification; Reactive processing; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA; ENGENHARIAS::ENGENHARIA QUIMICA; ENGENHARIAS